Tunable magnetization reversal and exchange bias in NiCr2O4 ceramics doped with non-magnetic ions. (December 2021) - Xie, L.; Huang, H.L.; Zhang, H.G.; Yu, J.Q.; Zhang, J.Z.; Lu, Y.L.
Abstract: The magnetization reversal and exchange bias (EB) effects were systematically investigated for nanocrystalline samples of NiCr2- x Ga x O4 ( x  = 0–1.0). The intrinsic temperature-induced magnetization reversal (TIMR) effect could be modulated by doping with Ga ions and controlling the particle size. The TIMR effect was closely related to the Griffiths phase observed in this system. Both the zero-field-cooling and field-cooling EB effects could be observed simultaneously within the doping range x  = 0.1–0.5. Upon doping with non-magnetic ions, the magnetic interactions of Ni–Cr and Cr–Cr were significantly diluted, which were further confirmed by specific heat measurements. Overall, the results highlight the potential to control the TIMR and EB phenomena by doping and controlling the particle size. Graphical abstract: Image, graphical abstract